PD-1 blockade in combination with zoledronic acid to enhance the antitumor efficacy in the breast cancer mouse model - Li, Yuan; Du, Yang; Sun, Ting; Xue, Huadan; Jin, Zhengyu; Tian, Jie (BMC cancer, 2018)
Blockade of PD-1 receptor may provide proof of concepts for the activity of an immune-modulation approach for the treatment of breast cancer (BC). Zoledronic acid (ZA) has been proven to inhibit angiogenesis, invasion, and adhesion of tumor cells. The aim of this study was to investigate the potential of monoclonal antibody against T cell checkpoint PD-1 in combination with chemotherapeutic drug ZA in BC mouse model. The 4 T1-fLuc mouse BC model was used in this study. The anti-tumor efficacy of anti-PD-1 antibody alone or in combination with ZA was monitored by measuring bioluminescence imaging (BLI) and tumor volume. At the end of study, the flow cytometry was used to determine the immune cell population in tumors after different treatment. The results showed that mice treated with the combination therapy of anti-PD-1 antibody plus ZA exhibited better antitumor response compared to untreated controls or single therapy with no obvious toxicity. Our study provides preclinical evidence for the enhanced BC treatment benefit through targeting co-signal molecules by combining anti-PD-1 antibody plus ZA treatment.